Analisis Dan Perancangan Sistem Informasi Pemesanan Produk Wedding Organizer Berbasis Web Pada Reva Pelaminan Jambi - Hidayat, M Irfan; Mulyono, Herry (LPPM Universitas Dinamika Bangsa, 2021)
Reva Pelaminan Jambi in promotion and order wedding organizer process still get trouble, such as : reservation services need time and difficulty in order, sometimes get error in processing reservation wedding organizer data, and limited promotion package information. The purpose of research is analyzing and design information systems reservation wedding organizer in Reva Pelaminan Jambi web-based using PHP programming language and MySQL database. Metodology of this research use waterfall model and unified model language using use case diagram, activity diagram, and class diagram. Conclusion of this system can be made easier for customers to order package online and processing data to computerized. Research advice are prototyped this system should be devised well and properly so that it will could be applied to Reva Pelaminan Jambi.